Diagnosing overtraining syndrome: A scoping review - Carrard, J.; Rigort, A.-C.; Appenzeller-Herzog, C.; Colledge, F.; Königstein, K.; Hinrichs, T.; Schmidt-Trucksäss, A. (Sports Health: A Multidisciplinary Approach, 2021)
Context: Overtraining syndrome (OTS) is a condition characterized by a long-term performance decrement, which occurs after a persisting imbalance between training-related and nontraining-related load and recovery. Because of the lack of a gold standard diagnostic test, OTS remains a diagnosis of exclusion.